Cytosolic DNA sensors regulating type I interferon induction - BOWIE, ANDREW (My University, 2011)
Type I interferon induction is a critical anti-pathogen response mediated by innate immune stimulation. While it has been appreciated for some time that the presence of pathogen DNA within a cell leads to a type I interferon response, it is only in the past few years that some of the key signalling proteins and DNA sensors that regulate this response have been uncovered. Here we review the nature of these DNA sensors, which includes a new family of pattern recognition receptors termed the `AIM2-like receptors (ALRs), and consider the implications of their discovery for understanding emerging principles of innate immune DNA sensing. Furthermore, we discuss how their discovery provides a rationale as to why accumulation of self-DNA mediates IFN-dependent autoimmunity.
PUBLISHED
Keywords: Type I interferon induction; Immunology, Inflammation & Infection